2020
DOI: 10.1038/s41598-020-64293-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Combinatorial Regimen of Garcinol and Curcuminoids for Non-alcoholic Steatohepatitis (NASH) in Mice

Abstract: Non-alcoholic steatohepatitis (NASH) is a progressive form of Non-alcoholic fatty liver disease (NAFLD), a chronic liver disease with a significant unmet clinical need. In this study, we examined the protective effects of Garcinia indica extract standardized to contain 20% w/w of Garcinol (GIE) and 95% Curcuminoids w/w from Curcuma longa (Curcuminoids) in a Stelic animal model (STAM) of NASH. The STAM mice developed steatosis, hepatocyte ballooning, and inflammation, which were significantly reduced by the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 81 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…Besides HCC, future work will aim to determine whether regionally increased histone acetylation can progress the severity of NAFLD to NASH and cirrhosis through dysregulation of genes involved in inflammation and fibrosis. Finally, several drugs undergoing preclinical and clinical trials for reducing liver steatosis and fibrosis in NAFLD will likely impact acetyl-CoA metabolism [ 53 ] and/or histone acetylation [ 54 56 ]. Accordingly, we observed that firsocostat [ 57 59 ], an acetyl-CoA synthetase inhibitor which blocks the use of acetyl-CoA for DNL, reduces oleic acid-induced ɣH2AX in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides HCC, future work will aim to determine whether regionally increased histone acetylation can progress the severity of NAFLD to NASH and cirrhosis through dysregulation of genes involved in inflammation and fibrosis. Finally, several drugs undergoing preclinical and clinical trials for reducing liver steatosis and fibrosis in NAFLD will likely impact acetyl-CoA metabolism [ 53 ] and/or histone acetylation [ 54 56 ]. Accordingly, we observed that firsocostat [ 57 59 ], an acetyl-CoA synthetase inhibitor which blocks the use of acetyl-CoA for DNL, reduces oleic acid-induced ɣH2AX in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro studies have reported the hepatoprotective, antioxidant, antisteatotic and antilipidemic, anti-inflammatory, anti-fibrotic, antitumor, and cholagogic effects of the main phenolic-based components and curcuminoids in CL. [11][12][13][14]26,27] Unfortunately, the potential targets and mechanisms of CL are still not clear at present. This study comprehensively investigated the therapeutic effect of main components of CL on hepatic fibrosis via network pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Remarkable hepatoprotective, anti-inflammatory, and anti-fibrotic effects of analogs of curcumin and non-curcuminoid constituents have also been reported. [13,14] Despite a series of studies on the biological activities of active components in CL, the potential targets and underlying mechanisms of CL in hepatic fibrosis remain largely unclear. Due to the effects of CL and its bioactives on hepatic fibrosis in researches and a variety of pathological processes involved, we therefore hypothesized that CL possibly exert a treatment effect by acting on multiple pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of GAR into anti-inflammatory therapy has started recently, although the factors behind its capabilities are still yet to be discovered [ 43 ]. GAR has previously shown to have reduced inflammatory markers like TNF- and NF- B in hepatic inflammation in the steatohepatitis-derived hepatocellular carcinoma of a mouse model (STAM) and LPS-induced inflammation in THP-1 cells in vitro [ 50 ]. The inhibition of inflammation by GAR is expected due to its ability to down-regulate NF- B and cyclooxygenase-2 (COX-2) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%